¿Es la tierra realmente redonda? - Costa Lima, Luiz; Pontificia Universidade Católica, Río de Janeiro (2013)
Profesor de literatura comparada en la Pontificia Universidade Católica, Río de Janeiro. Ha publicado Control of the Imaginary: Reason and Imagination in Modern Times (University of Minnesota Press, 1988), The Dark Side of Reason: Fictionality and Power (Stanford University Press, 1992), The Limits of Voice: Montaigne, Schlegel, Kafka (Stanford University Press, 1996), História. Ficção. Literatura (Companhia das Letras, 2006).